An Active Catalyst System Based on Pd (0) and a Phosphine-Based Bulky Ligand for the Synthesis of Thiophene-Containing Conjugated Polymers - Liu, Meifang; Liu, Li; Zhang, Zhihui; Wan, Meixiu; Guo, Huanmei; Li, Dan (Frontiers in Chemistry, 2021)
To address the limitations of conventional Pd catalysts in polymerization of thiophene-containing conjugated polymers, an active catalyst system based on Pd (0) and a phosphine-based bulky ligand L1, is explored systematically in Suzuki-Miyaura polymerizations using thiophene boronic acid pinacol ester as one of the monomers. This active catalyst is found very efficient in synthesizing a series of thiophene-containing linear and hyperbranched conjugated polymers. First, as a model example, coupling reactions between electron-rich/moderately hindered aryl or thienyl halides and thiophene boronic acid pinacol ester give excellent yields with lower catalyst loading, and can be completed in shorter reaction time, in relative to Pd(PPh3)4. Notably, high molecular weight thiophene-containing polymers are successfully synthesized by Suzuki-Miyaura polycondensation of 2,5-thiophene bis(boronic acid) derivatives with different dibromo- and triple bromo-substituted aromatics in 5-15 min.